DEVELOPMENT OF ALL FOUR-WHEEL STEERING SYSTEMS (Perner's Contacts, 2020)
The paper deals with a search of the currently very popular system of all four wheels for road vehicles, especially for passenger cars. It summarizes the historical shift of individual systems and describes their advantages and disadvantages a technical point of view of the structural unit. It also focuses on systems used in today's cars, which are still very rarely built into newly manufactured vehicles.
Keywords: all wheel steering; four wheel steering; mechanical steering; steering gear; electrohydraulic steering; electromechanical steering; electronic control unit; electromotor